Emotional Connotations of Musical Instrument Timbre in Comparison With Emotional Speech Prosody: Evidence From Acoustics and Event-Related Potentials - Liu, Xiaoluan; Xu, Yi; Alter, Kai; Tuomainen, Jyrki (Frontiers in Psychology, 2018)
Music and speech both communicate emotional meanings in addition to their domain-specific contents. But it is not clear whether and how the two kinds of emotional meanings are linked. The present study is focused on exploring the emotional connotations of musical timbre of isolated instrument sounds through the perspective of emotional speech prosody. The stimuli were isolated instrument sounds and emotional speech prosody categorized by listeners into anger, happiness and sadness respectively. We first analysed the timbral features of the stimuli, which showed that relations between the three emotions were relatively consistent in those features for speech and music. The results further echo the size-code hypothesis in which different sound timbre indicates different body size projections. Then we conducted an ERP experiment using a priming paradigm with isolated instrument sounds as primes and emotional speech prosody as targets. The results showed that emotionally incongruent instrument-speech pairs triggered a larger N400 response than emotionally congruent pairs. Taken together, this is the first study to provide evidence that the timbre of simple and isolated musical instrument sounds can convey emotion in a way similar to emotional speech prosody.